Cultural economics - Brinkman, Richard L. (New Delhi, 1981)
It is frequently noted and generally assumed in the literature, today, that the science of economics has yet to produce a general theory of econo mic development. However, such a theory would be of advantage in that the most serious economic anoma lies faced today have their roots of causation, as well as the source of solution, founded in the processes of economic development. The pro ces of economic development is on going and concerns not only the less developed countries but pertains to countries in the advanced stages of economic development as well. The author of this study contends that such a theory of economic develop ment is already at hand. Consequen tly, the need is not for origination but rather for the further advance and perfection of that which already exists. These objectives, the author argues, can be achieved through the methodology and theory contained in cultural economics. Cultural econo mics represents an attempt to con ceptualize and explain the processes of economic growth and develop ment in the context of culture evolu tion.
Keywords: Economic development